PENGARUH PERMAINAN TRADISIONAL LOMPAT TALI TERHADAP KEMAMPUAN MOTORIK KASAR PADA ANAK USIA 5-6 TAHUN DI TK KASIH IBU DESA KASIKAN KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Yani, Maya Putri; Indarto, Wusono; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : The purpose of this study is to study the effect of traditional rope jump games on rough motor skills at 5-6 years old children in kindergarten of Kasikan village of Tapung Hulu sub-district, Kampar regency during April 2017. The research used experimental method with one group pre-test post design -test design with a sample size of 20 children. The type of instrument used in this study is to use an observation sheet to record about the activities that occurred during the given treatment. Based on the results of hypothesis test obtained there is the influence of the Jump Rope game on the ability Motorik Kasar children aged 5-6 years in kindergarten Kasih Ibu Kasikan Village Tapung Hulu District Kampar regency. Obtained thitungsebesa value 24,405 with sig 0.000, because sig <0,05 hence can be concluded that there is influence of Lump Jump rope to ability Motorik Gross in child. In Hypothesis test can be seen t count = 24,405 > t table = 2.093. It can be interpreted that there is a significant influence on the game Jump Rope on the ability of Motorik Crude children aged 5-6 years in kindergarten Kasih Ibu Kasikan Village Tapung Hulu District Kampar district of 53.69%.Keywords : Rugged Motor Capability, Traditional Jump Rope Game.